1987
DOI: 10.1079/bjn19870047
|View full text |Cite
|
Sign up to set email alerts
|

The role of rumen protozoa in the utilization of paspalum (Paspalum dilatatum) hay by cattle

Abstract: 1. Six Friesian heifers (250 kg live weight) with permanent cannulas in the rumen and abomasum were allocated at random into two groups of three. One group was treated with Teric GN9 (ICI (Aust.) Ltd) to defaunate the animals during the first two of the four periods of the experiment, after which they were refaunated. The second group was treated with Teric at the end of the first two periods. The dietary treatments were: paspalum (Paspalum dilatatum) hay (4.1 kg/d) given alone and the hay supplemented with ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In addition, the decrease in urinary N excretion in PDFAUN lambs could also result from a greater proportion of urea-N output being recycled to the GIT and its increased sequestration for microbial protein synthesis in the rumen or hindgut or both. In agreement with our results, others (Ikwuegbu and Sutton, 1982;Punia et al, 1987) have also observed decreases in urinary N excretion as a result of defaunation. Total N losses were 5.2 to 9.0 g/d less (P = 0.004) in PDFAUN compared with FAUN lambs; as a proportion of N intake, PDFAUN lambs excreted 5.4 to 6.8 percentage units less (P = 0.06) N compared with FAUN lambs.…”
Section: N Balancesupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, the decrease in urinary N excretion in PDFAUN lambs could also result from a greater proportion of urea-N output being recycled to the GIT and its increased sequestration for microbial protein synthesis in the rumen or hindgut or both. In agreement with our results, others (Ikwuegbu and Sutton, 1982;Punia et al, 1987) have also observed decreases in urinary N excretion as a result of defaunation. Total N losses were 5.2 to 9.0 g/d less (P = 0.004) in PDFAUN compared with FAUN lambs; as a proportion of N intake, PDFAUN lambs excreted 5.4 to 6.8 percentage units less (P = 0.06) N compared with FAUN lambs.…”
Section: N Balancesupporting
confidence: 94%
“…Although complete defaunation was not achieved in the present study, substantial reductions in ruminal protozoal populations were achieved, coupled with positive responses in N utilization. Also, partial defaunation can be beneficial as it has been associated with a greater flow of NAN to the duodenum (Punia et al, 1987), improved feed:gain ratio in sheep (Ivan et al, 2004) and increases in milk yield in dairy cows (Moate, 1989).…”
Section: Ruminal Protozoal Numbers and Fermentation Characteristicsmentioning
confidence: 99%
“…Few trials give an indication on nitrogen urinary excretion [21,25,28,36]. Our data shows a lower nitrogen urinary excretion in ciliate-free animals as already observed [17].…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, the better feed conversion ratio after defaunation may be mainly attributed to the higher yield of metabolic utilisation of absorbed nutrients, for maintenance and growth [5]. Indeed, the duodenal nitrogen flow increased in ciliate free rams, and both the dietary and the microbial nitrogen flows contributed to this increase [23,28,30]. On the one hand, in ciliate-free animals, due to a lower proteolytic activity in the rumen, the ruminal degradation of dietary protein decreased and consequently the flow of intestinal by pass dietary protein increased [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as pointed out in the introduction, faunated ruminants are known to have higher ruminai NH 3 concentration (with the one exception of DEMEYER et al (1982); for review, see WILLIAMS and COLEMAN (1988) or VAN NEVEL and DEMEYER (1988)) than ciliate-free animals, and high ruminai NH 3 concentrations have even tend ed to be associated with large protozoal numbers (VEIRA et al, 1983; mainly in the dor sal sac of the rumen: YANG and VARGA, 1989). Thus, increased levels of rumen NH 3 -N in the presence of protozoa may possibly result from protozoal action on dietary and bacterial proteins (PUNIA et al, 1987).…”
Section: 1mentioning
confidence: 99%